Religieuze aspecten in beklagzaken van gedetineerden - van Eijk, Ryan (Religie & Samenleving, 2018)
Dutch detention law sees a detainee as a legal subject. As a result, detention law has a complaints procedure for detainees. Restrictions of the right to religion/philosophy of life during detention can be a reason to complain. However, the way in which religion/philosophy of life plays a role in these complaints is still an unexplored area. The article presents an exploratory study in which an inventory is made of the extent to which and in which way religion/philosophy of life plays a role in these matters in the period 2002-2016. This has been done on the basis of the database in which all appeal cases relating to a complaint are stored. In almost 2% of the cases, religion/philosophy of life appears to play a role. This mainly concerns problems regarding 1- food laws and 2- restriction in participation in religious activities, 3- the role of the spiritual caretaker or 4- cases in which religion/philosophy of life is part of the argumentation in the case.